2020
DOI: 10.1111/cogs.12908
|View full text |Cite
|
Sign up to set email alerts
|

What Does “Mind‐Wandering” Mean to the Folk? An Empirical Investigation

Abstract: Although mind-wandering research is rapidly progressing, stark disagreements are emerging about what the term "mind-wandering" means. Four prominent views define mind-wandering as (a) task-unrelated thought, (b) stimulus-independent thought, (c) unintentional thought, or (d) dynamically unguided thought. Although theorists claim to capture the ordinary understanding of mind-wandering, no systematic studies have assessed these claims. Two large factorial studies present participants (N = 545) with vignettes tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…This may explain why empirical studies have found that activities like walking (Oppezzo & Schwartz, 2014) help to generate creative ideas, and therefore suggests a new avenue for producing ideas in the laboratory and everyday life. Our results also support recent work, which suggests that mind wandering can be engaged with one’s external environment (Irving et al, 2020). Such coupled mind wandering may play an important functional role, insofar as it benefits from external constraints…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may explain why empirical studies have found that activities like walking (Oppezzo & Schwartz, 2014) help to generate creative ideas, and therefore suggests a new avenue for producing ideas in the laboratory and everyday life. Our results also support recent work, which suggests that mind wandering can be engaged with one’s external environment (Irving et al, 2020). Such coupled mind wandering may play an important functional role, insofar as it benefits from external constraints…”
Section: Discussionsupporting
confidence: 92%
“…Our work significantly advances the literature on mind wandering and creativity in two ways. First, we are the first to empirically study how a central form of mind wandering––freely moving thought (Christoff et al, 2016; Irving, 2016; Irving et al, 2020; Irving & Glasser, 2019; Seli et al, 2018)––relates to creative idea generation. Various theoretical models posit that freely moving thought and the divergent thought processes that people use to generate creative ideas belong to the same family of cognitive processes, since both involve a broad, associative, and exploratory mode of thinking (Christoff et al, 2016; Girn et al, 2020; Irving, 2021; Sripada, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A single-item probe might be useful for initial research into the relationship between freely moving thought and other well-established constructs related to mind wandering. For example, the relationship between the intentionality of mind wandering and freely moving thought remains unclear (although Irving et al, 2020, suggest that folk conceptualizations of mind wandering distinguish freely moving thought from intentionality). Preliminary investigations of these relationships might rely on a single-item measure of freely moving thought and only use more complex methods when there is evidence that more fine-grained assessments are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a handful of studies have tested the predictions of the Dynamic Framework (Alperin et al, 2021; Irving et al, 2020; Kam et al, 2021; Mills, Herrera-Bennett, et al, 2018; O’Neill et al, 2021; Smith et al, 2022). With the exception of Alperin et al (2021), these studies focus more on the thought probe methodology itself, its relation to existing measures of mind wandering, and its nature as a psychological construct (Kam et al, 2021; O’Neill et al, 2021; Smith et al, 2022).…”
mentioning
confidence: 99%
“…They suggest instead that free movement in thought from one mental state to the next with relatively few constraints is an essential property of mind wandering. Whereas this approach captures an intuitive sense of the term mind wandering (Irving et al, 2020), it does not seamlessly align with the above operational definitions (Seli, Kane, Metzinger, et al, 2018).…”
Section: What Is Mind Wandering?mentioning
confidence: 94%